2011
DOI: 10.1186/1471-2407-11-402
|View full text |Cite
|
Sign up to set email alerts
|

Unstaged cancer in the United States: a population-based study

Abstract: BackgroundThe current study examines unstaged disease for 18 cancer sites in the United States according to the influence of age, sex, race, marital status, incidence, and lethality.MethodsAnalyses are based on 1,040,381 male and 1,011,355 female incident cancer cases diagnosed during 2000 through 2007. Data were collected by population-based cancer registries in the National Cancer Institute's Surveillance, Epidemiology, and End Results Program.ResultsThe level of unstaged disease was greater in more lethal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 24 publications
12
41
1
Order By: Relevance
“…This study also found higher prevalence of blacks with unstaged cancers or cancers with missing stage at diagnosis for the four main cancer types compared with whites, as suggested by results from previous studies (4244). For example, Klasen and colleagues (43) found that patient characteristics of being older and black increased the likelihood of having unstaged/missing data.…”
Section: Discussionsupporting
confidence: 88%
“…This study also found higher prevalence of blacks with unstaged cancers or cancers with missing stage at diagnosis for the four main cancer types compared with whites, as suggested by results from previous studies (4244). For example, Klasen and colleagues (43) found that patient characteristics of being older and black increased the likelihood of having unstaged/missing data.…”
Section: Discussionsupporting
confidence: 88%
“…There is some evidence that unstaged diagnoses in the U.S. are more prevalent with lethal cancers and in certain patient groups including the elderly. [47] However, we were unable to evaluate this within the context of the present report. The influence of access to treatment on cancer outcome could not be evaluated as information on medical insurance coverage was not available from registry data in Guam and Hawaii.…”
Section: Discussionmentioning
confidence: 63%
“…These findings suggest that advancing age and the presence of comorbidities were associated with more conservative treatment with less complete diagnostic assessment, which is then associated with ‘unknown’ stage 36 7 Among the group of patients who received prostate procedures other than RP and had a hospital-reported prostate cancer diagnosis within 4 months of the initial diagnosis, those who were older at diagnosis, lived in socioeconomically disadvantaged areas, had prostate procedures other than multiple procedures plus imaging, who were admitted to private hospitals, or who had a day-only admission were more likely to have ‘unknown’ stage recorded in the NSWCR.…”
Section: Discussionmentioning
confidence: 99%